Managing human, environment and natural resources for sustainability proceedings of the Universiti Malaysia Terengganu 8th International Annual Symposium on Sustainability Science and Management held on 3-4 May 2009 in Kuala Terengganu, Terengganu - Asyraf Ab. Rahman (Penerbit Universiti Malaysia Terengganu, 2009)
This volume contains the Proceeding of the UMT 8th Annual Symposium on Sustainability Science and Management, which was held in Kuala Terengganu from May 3rd to 4th in 2009. About 200 participants from local and international countries attended the symposium and 150 papers were presented, 110 of them as oral presentations and others as posters.